The influence of internal and external visual imagery on self-confidence in learning gymnastics - Rifky Riyandi Prastyawan; Wawan Sundawan Suherman; Ahmad Nasrulloh (Jurnal Cakrawala Pendidikan, 2023)
Students must have high self-confidence in learning physical education because self-confidence affects individual motor skill performance. The purpose of this study was to reveal differences in the influence of internal and external visual imagery on students' self-confidence in learning gymnastics with cartwheel material. This research is multiple linear regression experimental research. The number of samples in this study was 68 students. Actions are carried out by integrating internal and external visual imagery exercises in gymnastic learning. The data collection technique uses a self-confidence scale as an instrument. Data were analyzed using an independent sample t-test with a significance level of 0.05. The results showed that internal and external visual imagery had a significant effect on students' self-confidence (p=0.000 0.05), but there was a significant difference between internal and external visual imagery training (p=0.027 0.05) so that the internal visual imagery training method is better than the external imagery method (M=71.2941 67.8824). The results of this study indicate that students' self-confidence in performing wheel motion skills can be increased through internal and external visual imagery exercises that are integrated into the learning process, but internal visual imagery training methods are preferred.